Reseña del libro Costos y Gestión 5.0., de Marcelo Podmoguilnye, Julio Marchione, Daniel Farré, Juan Pott Godoy y Gustavo Metilli CABA, La Ley, 2023, ISBN978-987-03-4489-6 (Costos y Gestión, 2023)
Reseñas bibliográficas